Influence of splenectomy on the biodistribution of technetium-99m dimercaptosuccinic acid (99mTc-DMSA) in rats - Açucena,Maria Kadja Meneses Torres (2008)
This study aimed to evaluate if the splenectomy alters the biodistribution of 99mTc-DMSA and renal function in Wistar rats. The animals were separated in the groups: splenectomy (n = 6) and control (n = 6). After splenectomy (15 days), the administration of 0.1ml of 99mTc-DMSA IV (0.48 MBq) was carried out. Thirty minutes later, kidney, heart, lung, thyroid, stomach, bladder and femur and samples of blood were isolated. The organs were weighed, counted and the percentage of radioactivity /g (%ATI/g) determined. Serum urea and creatinine, hematocrit, leukocytes and platelets were measured. Statistics by t test (p<0.05) was done. There was a significant reduction in %ATI/g in kidney and blood (p<0.05) of splenectomized animals, a significant increase (p<0.05) of urea (88.8 ± 18.6 mg/dL) and creatinine (0.56 ± 0.08 mg/dL), compared to the controls (51.5±1.6, 0.37±0.02mg/dL, respectively), as well as increase in platelets and leucocytes, and hematocrit reduction. The analysis of the results indicates that in rats, splenectomy seems to alter the renal function and the uptake of 99mTc-DMSA.